Design and test of self-propelled citrus seedling pots filling and placing machine - Xu, Qinchao; Li, Shanjun; Zhang, Jian; Zhu, Jiating; Pan, Haibing (International Journal of Agricultural and Biological Engineering, 2023)
In order to address the problem of citrus seedling pot filling and transporting which is time-consuming and labor-intensive in China, a scheme for seedling pot filling and placing was proposed, and a self-propelled citrus seedling pot filling and placing machine was designed which can fill and place 48 pots at one time. Firstly, the rotary hopper door mechanism was designed, the movement of the hopper door was analyzed, and the connection between the opening size and the movement time of the hopper door was determined. Then, the transmission system of the machine was designed, the power consumption of the hopper movement and substrate stirring were calculated, and the power requirement of the transmission system was determined. The lifting structure of the seedling pots frame was analyzed, the size of the flipping structure of the cover plate was calculated, and the seedling pots frame was designed. After that, the substrate flow rate curve was measured through the substrate flow rate experiments, and the hopper-controlled movement speed was calculated. Furthermore, the experimental prototype was manufactured and tested. The test results indicate that the filling number of pots was 48 one time, the filling time was 30 s, and the seedling pots were fully filled and placed in order. The average filling mass of the seedling pots was 2.23 kg, and the average mass variation coefficient was 2.7%. The substrate mass which is scraped out is 0.81 kg, accounting for 0.76% of the total filling mass at one time. This designed machine had a reasonable structure and high filling efficiency. The reseach can provide a reference for the development and optimization of the citrus seedling pots filling and transporting machine.Keywords: agricultural machinery, design, experiments, fillingmachine, placing machineDOI: 10.25165/j.ijabe.20231601.7817Citation: Xu Q C, Li S J, Zhang J, Zhu J T, Pan H B. Design and test of self-propelled citrus seedling pots filling and placing machine. Int J Agric & Biol Eng, 2023; 16(1): 104–110.